Coastal Abrasion Disaster Mitigation Strategy in Dumai City through Community Empowerment Program - Santosa, Fajar Julian; Agustiawan; Audina Reihan; Iwed Mulyani; Muhammad Raushan Fikri; Muhammad Farid Arifani; Ramadhan Imam Dzaky; Anggoro Seto Priambodo; Gatra Wiraandika (Prospect Publishing, 2024)
Abrasion is a process of coastline erosion due to continuous increase in sea waves that causes land loss and damages coastal ecosystems. Abrasion on the coast of Dumai City has caused various problems including land loss, difficult access for fishermen to go to sea, and damage to fishing boats due to exposure to abrasion waves. This study was conducted using a qualitative descriptive approach with cases in the coastal area of ​​Dumai City in Mundam Village. Data collection was carried out through in-depth interviews with 5 informants, observation, and documentation to strengthen the data collected. Interactive model data analysis was used in this study. The results of the study showed that the mitigation strategy carried out on the coast of Dumai City used an empowerment approach by raising awareness of coastal communities about the dangers of abrasion which not only impacts land erosion, but can further threaten the livelihoods and lives of fishermen. This activity includes several stages: (1) rehabilitation and planting of mangroves; (2) construction of breakers and wave breakers; (3) strengthening communities through education and training; and (4) monitoring and evaluation.